Protein Urine Sebagai Penanda Preeklampsia Dalam Kehamilan - Antu, Yuniarty (Madu : Jurnal Kesehatan, 2024)
Maternal mortality rate in Indonesia still high and the prevalence of perinatal deaths is four times higher in cases of preeclampsia/eclampsia. Urine protein tests still used to assess preeclampsia in pregnant women. This study aimed to evaluate proteinuria in pregnant women-based parity, age and weeks of pregnancy in Gorontalo. This study used descriptive with cross sectional study based on inclusion and exclusion criteria. The results showed that 50% of subjects experienced proteinuria with values of +1 (45.8%) and +2 (4.2%). The high incidence of proteinuria in pregnant women means that urine protein tests as easy and fast methods help to detect preeclampsia in pregnant women.